2022
DOI: 10.21203/rs.3.rs-1325039/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring the skin microbiome after a 3% aqueous hydrogen peroxide (H2O2) dysbiosis using ATP biofluorescence

Abstract: Background: Since its complete mapping in 2008, the human skin microbiome has become an important area of research related to skin health. The human skin is populated by an environment of microorganisms, fungi, insects, and viruses that is collectively known as the microbiome. Measuring the skin’s microbial diversity can be done but is a sophisticated technique that is performed using expensive instruments that can detect the 16S ribosomal RNA of the microorganisms. Finding more rapid and less costly methods t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Since the groundbreaking studies by Elizabeth Grice at the University of Pennsylvania to map the total human skin microbiota, interest in the relationship between the microbiome and the skin’s health have exploded. 1–3 Grice’s studies demonstrated clearly that different areas of the body carry different populations of microorganisms depending on several factors such as body moisture, oil content and exposure to ultraviolet radiation, among others. Interest in the role of the skin’s microbiome and microbiota and how they relate to the skin’s health are important and continue to expand.…”
Section: Introductionmentioning
confidence: 99%
“…Since the groundbreaking studies by Elizabeth Grice at the University of Pennsylvania to map the total human skin microbiota, interest in the relationship between the microbiome and the skin’s health have exploded. 1–3 Grice’s studies demonstrated clearly that different areas of the body carry different populations of microorganisms depending on several factors such as body moisture, oil content and exposure to ultraviolet radiation, among others. Interest in the role of the skin’s microbiome and microbiota and how they relate to the skin’s health are important and continue to expand.…”
Section: Introductionmentioning
confidence: 99%